Drivers of high-cost persistence in rural China: A population-based retrospective study - Wang, Chenzhou; Lu, Shan; Zhang, Yan (Frontiers in Public Health, 2022)
Purpose High-cost patients account for over 70% of total health expenditures in rural China and have become a key focus of health insurers. Persistently high-cost patients constitute a substantial proportion of medical resources. Hence, exploring high-cost persistence (HCP) and what drives it is considered meaningful and necessary. Patients and methods A population-based retrospective study was carried out. The annual healthcare utilization data of Dangyang New Rural Cooperative Medical Scheme from 2012 to 2017 were analyzed. Patients in the top 10% of spending in a given year were considered high-cost patients. Persistence level was estimated using Markov matrices. A total of 19,405 patients categorized as high-cost patients in 2016 were divided into two groups according to whether or not they kept high-cost status in 2017. Finally, a multilevel logistic regression model was used in examining the determinants of HCP. Results On average, about 31.48% of high-cost patients each year still maintained high-cost status in the subsequent year from 2012 to 2017. The elderly (OR = 2.150), families with more non-labor members (OR = 2.307), families applying for subsistence allowances (OR = 1.245), and patients with blood and immune diseases (OR = 2.614) or malignant tumors (OR = 2.077) were more likely to maintain high-cost status. Hospitalization frequency was found to be a mediator. Conclusion About one-third of high-cost patients in a given year had persistently high cost status in the subsequent year. Health status and family support were considered the main drivers of HCP. High inpatient service utilization as a mediator was a prominent manifestation of persistently high-cost patients. The accurate identification of persistently high-cost patients is the basis for our management.